2014
DOI: 10.1097/sla.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Recurrence of Pancreatic Solid Pseudopapillary Tumors After Surgical Resection

Abstract: More specific pathologic descriptions need to be employed in pathologic report forms to provide proper information to predict SPT recurrence after resection. Future studies emphasizing the standardized pathologic evaluation of pancreatic SPTs may unveil the enigmatic nature of pancreatic SPTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 29 publications
9
144
5
Order By: Relevance
“…Few previous studies of SPPN have separately analyzed adults and children . The main features of SPPN in children are a higher frequency of abdominal pain and fewer incidental diagnoses (22%) . An exhaustive review of the literature shows that SPPN is equally distributed in the head, body, and tail of the pancreas and have a mean size of 7 cm (Supplementary Table SI).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Few previous studies of SPPN have separately analyzed adults and children . The main features of SPPN in children are a higher frequency of abdominal pain and fewer incidental diagnoses (22%) . An exhaustive review of the literature shows that SPPN is equally distributed in the head, body, and tail of the pancreas and have a mean size of 7 cm (Supplementary Table SI).…”
Section: Discussionmentioning
confidence: 93%
“…Seven patients (13.7%) relapsed, a median of 43 months after initial surgery. [–94] One patient experienced two relapses at a 10.6‐month interval. During a median follow‐up of 65 months [0.3–221], recurrences were found in five patients by routine follow‐up imaging (Computed tomography CT or Magnetic Resonance Imaging MRI), by the occurrence of hypogastric pain in one patient, and by self‐examination (mass) in one patient.…”
Section: Resultsmentioning
confidence: 99%
“…Outpatient records combined with telephone interviews were used for follow-up. The criteria of SPN were defined as malignant if it demonstrated extrapancreatic invasion, distant metastases, pancreatic parenchymal invasion, peripancreatic fat tissue infiltration, lymph node involvement, capsular invasion, or perineural or vascular invasion [47]. Patient status was due to the time of last follow-up as follows: no evidence of disease, alive with disease, dead of disease, surgical mortality, and dead of other causes.…”
Section: Methodsmentioning
confidence: 99%
“…Solid pseudopapillary tumors of the pancreas affect primarily young women, suggesting that hormonal factors contribute to the tumor growth [4,5,8]. In the current study, symptoms were reported at a woman of 28 years of age, an age at which female hormones and their receptors such as progesterone, estrogen are very active and might play a role in the development of solid pseudopapillary tumor of the pancreas [9,10].…”
Section: Discussionmentioning
confidence: 99%